ANALISA PERBANDINGAN SOFTWARE DEVELOPMENT MODEL ANTARA METODE SCRUM DAN METODE INCREMENTAL: ANALISA PERBANDINGAN SOFTWARE DEVELOPMENT MODEL ANTARA METODE SCRUM DAN METODE INCREMENTAL - Andriani, Eka Oktavia; Dwi Wahyuni , Evi; Nurul Ramadha , Firdatul; Zalman Alfarizy, Achmad (Himpunan Dosen Ilmu Komputer, 2024)
This study compares two popular methods in software development, Scrum and the incremental model. Scrum, as part of Agile, emphasizes short iterations (sprints) and intense team collaboration to deliver usable products incrementally. In contrast, the incremental model focuses on developing software gradually, where each stage produces a portion of the system's functionality that will eventually be integrated into a complete product. This comparative analysis explores the fundamental principles, processes, outputs, team collaboration, strengths, and weaknesses of both methods. The findings indicate that Scrum is suitable for projects with changing requirements and well-coordinated teams, while the incremental model is more appropriate for projects with more stable requirements and teams that require flexibility in tailoring the process. A deep understanding of the strengths and weaknesses of each method can aid in making informed decisions for effective, efficient, project-tailored software development endeavors, thereby enhancing the chances of success, stakeholder satisfaction, and competitiveness in today's dynamic business environment. Keywords: Software Model, Scrum Method, Incremental Method